2015
DOI: 10.4306/pi.2015.12.2.268
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Depression, Anxiety, Somatization, Personality and Symptoms of Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Hyperplasia

Abstract: This study investigated the relationship of personality, depression, somatization, anxiety with lower urinary tract symptoms suggestive of benign prostatic hyperplasia (LUTS/BPH). The LUTS/BPH patients were evaluated with the International Prostate Symptom Score (IPSS), 44-item Big Five Inventory (BFI), the Patient Health Questionnaire-9 (PHQ-9), the PHQ-15, and 7-item Generalized Anxiety Disorder Scale (GAD-7). The LUTS/BPH symptoms were more severe in patients with depression (p=0.046) and somatization (p=0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…It was observed that the higher the subjective health status, the better the HRQOL of such patients. As aforementioned, patients with BPH tend to suffer from disabilities in daily life due to lower urinary tract symptoms, which may cause depression, anxiety, and stress and thus negatively affect subjective health status [ 38 , 39 , 40 ]. Symptoms of BPH, unlike other chronic diseases such as hypertension and diabetes, are often perceived as less serious.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the higher the subjective health status, the better the HRQOL of such patients. As aforementioned, patients with BPH tend to suffer from disabilities in daily life due to lower urinary tract symptoms, which may cause depression, anxiety, and stress and thus negatively affect subjective health status [ 38 , 39 , 40 ]. Symptoms of BPH, unlike other chronic diseases such as hypertension and diabetes, are often perceived as less serious.…”
Section: Discussionmentioning
confidence: 99%
“…12 This nature was proved by Barbara Pietrzyk et al in 2015 and in addition to the relationship of LUTS with anxiety and somatization by Jun Sung Koh and associates. 13,14 Age related LUTS\BPH was mentioned by Weiyu Zhang et al while beside the age related LUTS, the role of the medical management of BPH and decreasing the resultant LUTS were also reported by Farhad Fakhrudin and colleagues. 15,16 Improvement of LUTS and inconsequence depression, anxiety and psychiatric morbidity was documented for both medical and surgical treatment by Kia Fatt Quek et al (in the contrary of our study).…”
Section: Discussionmentioning
confidence: 95%
“…Many patients with andrological diseases have different degrees of mental and psychological problems. The incidence of depression and anxiety disorders in patients with andrological diseases is significantly higher than that in the general population [ 17 , 35 , 36 ]. Psychological factors are often important factors influencing disease outcomes and communication between physicians and patients, especially for patients with andrological diseases [ 37 ].…”
Section: Discussionmentioning
confidence: 99%